Developmental dynamics of post-selection thymic DN iNKT. - Maryam Yassai; Brian Cooley; Jack Gorski (PLoS ONE, 2012)
Invariant natural killer T (iNKT) cells develop in the thymus and branch off from the maturation pathway of conventional T cell at the DP stage. While different stages of iNKT cellular development have been defined, the actual time that iNKT cell precursors spend at each stage is still unknown.Here we report on maturation dynamics of post-selection DN iNKT cells by injecting wild-type DP(dim) thymocytes into the thymus of TCRα(-/-) mice and using the Vα14-Jα18 rearrangements as a molecular marker to follow the maturation dynamics of these cells.This study shows that the developmental dynamics of DN iNKT cells in DP(dim) are very rapid and that it takes less than 1 day to down-regulate CD4 and CD8 and become DN. These DN cells are precursors of peripheral DN iNKT cells and appear in the spleen in 1-2 days. Thymic DN iNKT residents are predominantly derived from cells that quickly return from the periphery. The expansion of a very small subset of DN iNKT precursors could also play a small role in this process. These data are an example of measuring T cell maturation in the thymus and show that the maturation dynamics of selected DN iNKT cells fall within the same general time frame as conventional αβ T cells.